Analysis of bioactive phytochemical compounds of two medicinal plants horsetail Equisetum arvense and Alchemila valgaris seeds by using Gas Chromatography-Mass Spectrometry and Fourier-Transform Infrared Spectroscopy - Altameme, Huda Jasim; Hameed, Imad Hadi; Abu-Serag, Nidaa Adnan (Malaysian Society of Applied Biology, 2015)
Twenty five bioactive phytochemical compounds were identified in the methanolic extract of Equisetum arvense and Alchemila valgaris. The identification of phytochemical compounds is based on the peak area, retention time molecular weight and molecular formula. GC/MS analysis of Equisetum arvense revealed the existence of the Cyclohexene, 4-isopropenyl-1- methoxymethyl, α-D-Glucopyranoside, O-α-D-Glucopyranosyl, Paromomycin, 3,6,9,12-Tetraoxatetradecan-1-ol, Bicyclo[3.2.1] oct-6-ene-6,8-dimethanol, 1,7-dimethyl-4isopropyl, 2-Undecanone, 3-N,N-Dimethyllaurylammonio) propanesulfonate, d-Mannose, 3-O-Methyl-d-glucose, 9,10-Secocholesta-5,7,10(19)-triene-3,24,25-triol, Benzaldehyde, 2- chloro-4-hydroxy-3, Cyclopropa[3,4]cyclopenta [1,2-a]naphthalene, Furo[2,3-b]quinoline,4,6,7-trimethoxy, 2(1H)- Phenanthrenone. GC/MS analysis of Alchemila valgaris revealed the existence of the Levoglucosenone, Spirost-8-en-11- one, 3-hydroxy, Ethanol, 2-(9-Octadecenyloxy), 2,7-Diphenyl-1,6dioxopyridazino[4,5:2,3]pyrrolo, Estra-1,3,5(10)-trien-17β- ol, Octadecanal,2-bromo, Ethyl 9,12,15-octadecatrienote, 3-Pyridinecarboxylic acid,2,7,10-tris(acetyloxy)-1, 5HCyclopropa[ 3,4]benz[1,2-e]azulen-5-one, Stigmastan-3,5-diene and Tocopherol. It contains chemical constituents which may be useful for various herbal remedy as anti-inflammatory, analgesic, antipyretic, cardiac tonic and antiasthamatic. The FT-IR analysis of both Equisetum arvense and Althaea rosea seeds proved the presence of Alkenes, Aliphatic fluoro compounds, Alcohols, Ethers, Carboxlic acids, Esters, Nitro Compounds and Alkanes.